LERNAEA DIVERSITY AND INFECTION IN INDIAN AND CHINESE CARPS UNDER SEMI-INTENSIVE CULTURE CONDITIONS IN LAHORE, PUNJAB - Z. Iqbal; A. Shafqat; F. Haroon (Journal of Animal and Plant Sciences, 2012)
Indian and Chinese carps, Labeo rohita, Catla catla; Ctenopharyngodon idella; Hypophthalmichthys molitrix and Aristichthys nobilis were obtained from Punjab University Fish Research farms Lahore. These fishes were examined for parasitic infection, lernaeasis. Lernaea cyprinacea (L.) was the most prevalent parasite infecting these five fish species (comprising 88.48-100% population). In addition to L. cyprinacea; Lernaea polymorpha (Yu, 1938); Lernaea oryzophila (Monod, 1932) were found on L. rohita and C. idella.  Lernaea ctenopharyngodonis was found on C. idella only. Prevalence of Lernaea was 68.9% and 63.6% in L. rohita and C. catla respectively and 78.1% in C. idella; 66.7% in A. nobilis and 9.1% in H. molitrix. Mean intensity was 17.3; 9.2; 6.91; 1.0 and 3.0 in these fishes respectively. The prevalence was highest in February which dropped towards April. The abdomen and the base of pectoral, pelvic and anal fin of these fishes seem the most common site of attachment of Lernaea than any other area of the body of the fish.  As 52.05 to 57.80% parasites were attached here. Lernaea diversity and infection in carps reared in earthen ponds under semi-intensive culture conditions are discussed.
Keywords: Lernaea cyprinacea; infection; diversity; culturable carps